Bibliografía sobre investigaciones marinas, oceanográficas, geológicas y atmosféricas en el Parque Nacional Isla del Coco y aguas adyacentes, Pacífico de Costa Rica - Cortés, Jorge (Revista de Biología Tropical, 2012)
Bibliography on marine, oceanographic, geological and atmospheric research at Isla del Coco Nacional Park and adjacent waters, Pacific Costa Rica. Isla del Coco (also known as Cocos Island), Pacific Costa Rica, has been visited and written about since the 16th Century, and since the late 1800’s many expeditions and scientists have carried out research in the Island. Here I compiled publications on marine biological, geological, oceanographic and atmospheric research done at Isla del Coco. A list of 599 scientific papers and chapters were compiled, together with 41 books, reports, Special Issues, theses and web sites, and ten historic books with descriptions of marine animals or environemnets. A mayority of the publications (425 or 66.4%) are related to marine biodiversity topics (species descriptions and lists of species); the most published groups are gastropods (81 papers), decapods (67) and bony fishes (66). There are no publications of several groups of animals that have been observed in the Island, for example free-living flat worms, parasites and nemerteans among others. Other topics with a large number of publications are, biogeography with 65, ecology (61) and geology (48); the most studied ecosystem are coral reefs with 14 papers. More publications are needed on many topics, such as impact of ilegal fishing and climate change on Isla del Coco National Park marine flora and fauna. Citation: Cortés, J. 2012. Bibliografía sobre investigaciones marinas, oceanográficas, geológicas y atmosféricas en el Parque Nacional Isla del Coco y aguas adyacentes, Pacífico Costa Rica. Rev. Biol. Trop. 60 (Suppl. 3): 363-392. Epub 2012 Dec 01